PENGARUH TALENT MANAGEMENT TERHADAP JOB SATISFACTION: TINJAUAN LITERATUR - Clarissa Sunaryo , Alda; Kharenina Augustine, Annisa; Firmansyah, Yohanes (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Start-up companies in Indonesia are growing rapidly and this development supported by technological developments that continue to increase. The rapid development of technology and start-up companies, the need for human resources is also increasing. This matter has triggered the emergence of new professions that are increasingly found among young millennials. The emergence of new professions in start-up companies in the industrial era 4.0 encourages everyone to continue to develop themselves to maintain their job or get a better job. Self-development through formal education that has been achieved is not enough to meet the demands of work and positions in a company, so training and career development are needed. This training and career development is included in one of the talent management processes for employees to provide new skills to employees and can make employees like their work and tasks so that employees feel satisfied with their work. The research method used in this study is the literature review method. The data was collected from previous studies and literature on talent management and job satisfaction identified through various electronic databases. Based on the results of this literature review, it shows that talent management has a positive and significant influence on job satisfaction. This research can be the initial basis for further research on the influence of talent management on job satisfaction.